ВИКОРИСТАННЯ АКТИВНИХ ФОРМ ТА МЕТОДІВ ВИКЛАДАННЯ ПЕДАГОГІЧНИХ ДИСЦИПЛІН У ПІДГОТОВЦІ МАЙБУТНІХ УЧИТЕЛІВ - Пащенко, Майя (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті обґрунтовано сутність та зміст організації активної пізнавальної діяльності студентів у вищій педагогічній школі. Представлено сучасні вимоги до професійної підготовки майбутніх учителів у контексті активізації їх пізнавальної діяльності. Доведено доцільність застосування активних форм та методів навчання у процесі викладання педагогічних дисциплін. Визначено та охарактеризовано методи активного викладання педагогічних дисциплін. Виокремлено власні рекомендації щодо використання дидактичних ігор у підготовці майбутніх учителів. В статье обоснована сущность и содержание организации активной познавательной деятельности студентов в высшей педагогической школе. Представлены современные требования к профессиональной подготовке будущих учителей в контексте активизации их познавательной деятельности. Доказана целесообразность применения активных форм и методов обучения в процессе преподавания педагогических дисциплин. Определены и охарактеризованы методы активного обучения педагогических дисциплин. Выделены собственные рекомендации по использованию дидактических игр в подготовке будущих учителей. The essence and content of organization the active cognitive activity of students in higher educational school are explained in the article. Modern requirements for future teachers training in the context of activation of their cognitive activity are presented. The expediency of usage the active forms and teaching methods in the process of teaching the pedagogical subjects is proved. The experience of application the active forms of organization the teaching and cognitive activity of future teachers during their professional training are given. Methods of active teaching the pedagogical subjects are defined and characterized. Own recommendations on the use of didactic games in future teachers training were determined. Based on the analysis of educational literature and own pedagogical experience it was suggested to use in teaching pedagogical subjects such didactic games as «Pedagogical hockey», «Pedagogical vocabulary», «Blitz-Tournament», «Pedagogical dispute», «Journey», «Experts», etc. We offer detailed recommendations for every didactic game.